EVALUASI KEBIJAKAN PROGRAM PEMBERDAYAAN MASYARAKAT KELURAHAN (PPMK) DI KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA PROVINSI KALIMANTAN TIMUR - Selvia Junita Praja; Margaretha Rumbekwan; Muhammad Ibrahim (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
ABSTRACT. Mayor of North Penajam Paser District made a Community Empowerment Program Policy of the Urban Village with an allocation of 200 million rupiah per Urban Village. The Urban Village that began implementing PPMK in 2016 were hindered by new regulations that urban village are sub-districts’ device and have to wait for new regulations from the Regional Government. Regent Regulation No. 19 of 2017 concerning PPMK has been ratified but PPMK has not been implemented due to the deficit of APBD. Likewise, what happened in 2018, only 5 out of 19 urban villages in Penajam sub-district carried out PPMK, so that in the implementation of PPMK is experiencing a policy failure every year. Based on these thoughts, the researcher conducted a research with purpose to evaluating the policy. The research design used is qualitative research with descriptive methods. Researchers used data collection techniques through interviews, observation and documentation. Determination of the validity of the data by triangulating techniques and triangulation of sources. Based on the research conducted, it can be concluded that PPMK's policies do not run optimally because the policy implementers do not have commitment and poor coordination forms so that inconsistencies happened. Likewise with the unpreparedness of the PPMK fund budget, thereby reducing the achievement of policy objectives. The researcher suggests that local governments maximize the task of district level counterparts. Improve the PPMK budgeting mechanism to become a matching fund from the central government urban village fund. And provide sanctions to urban villages that do not implement PPMK. Keywords : public policy, policy evaluation, urban village funds, PPMK